2019
DOI: 10.2147/copd.s205543
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of noninvasive ventilation on the coordination between breathing and swallowing in patients with chronic obstructive pulmonary disease</p>

Abstract: Purpose As shown in our previous study, inspiration after swallowing (SW-I) increases during the bi-level positive airway pressure ventilation (BiPAP) in healthy subjects because swallowing-associated non-inspiratory flow (SNIF) triggers inspiratory support, while SW-I during continuous positive pressure ventilation (CPAP) is rare. In the present study, we evaluated the coordination between breathing and swallowing during spontaneous breathing, BiPAP, and CPAP in patients with chronic obstructive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The median (range) number of words between breaths was 5 (4-7) for the neuromuscular subjects on NIV, significantly fewer than 11 (8)(9)(10)(11)(12)(13) for the matched control subjects.…”
Section: Resultsmentioning
confidence: 90%
“…The median (range) number of words between breaths was 5 (4-7) for the neuromuscular subjects on NIV, significantly fewer than 11 (8)(9)(10)(11)(12)(13) for the matched control subjects.…”
Section: Resultsmentioning
confidence: 90%
“…MWST, modified water swallowing test; EMG, electromyography; HFNO, high flow nasal oxygen; LFNO, low flow nasal oxygen; ml, milliliters; min, minute; LPM, liters per minute test, the mean expiratory time in one minute was significantly longer in the HFNO group (41.5 ± 4.0 s in HFNO vs 39.2 ± 2.9 s in LFNO, p < 0.001). However, there was no difference in the respiratory rate (19.5 [17,21] rates per minute (rpm) in HFNO vs 20 [18,24] rpm in LFNO, p = 0.068) during the swallowing test (Table 2).…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, the lower subglottic pressure slowed pharyngeal transit time in tracheostomized patients, potentially contributing to pharyngeal residue accumulation and aspiration [ 19 , 20 ]. HFNO, on the other hand, produced positive airway pressure, which enhanced subglottic pressure and may have improved swallowing efficiency [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with either the I-SW pattern or the SW-I pattern were associated with a higher frequency of exacerbation [ 29 ]. A recent study showed the effectiveness of continuous positive pressure ventilation (CPAP) to decrease SW-I frequency and normalize the timing of swallowing [ 30 ]. While this discoordination has been well evaluated, tongue strength in COPD patients had yet to be evaluated.…”
Section: Discussion/conclusionmentioning
confidence: 99%